The labour situation of the graduates in Teaching in Physical Education: guarantee of quality - Mª Carmen Campos Mesa; Santiago Romero Granados; Gloria González Campos (FEADEF, 2010)
The introduction of the European Higher Education Area in a new culture of quality in Higher Education, makes us ask about the aspects that give quality to it. Among the quality factors in Higher Education we can find: University guidance and analysis of the graduate´s incorporation into the labour world. In this article we present the research we did in conducted at the six classes of graduates of Teaching in Physical Education from the University of Seville (N = 292). From the data we obteined, we can observe that 95% of the surveyed population does not ask for work or professional guidance during their degree and 63% of the surveyed population find their first job connected with the world of sport and physical activity, while 37% of this population has a work connected with other topics. Thus, we can conclude that most graduates of Teaching in Physical Education do not receive guidance for their incorporation into the labour world. This is why no everygraduate can get a job connected with the world of sport and physical activity.